Pengembangan Sistem Penghitung Takaran Air untuk menentukan Tingkat Kematangan Nasi menggunakan Regresi Linier berbasis Embeded System - Anisa Awalia Rizky; Dahnial Syauqy; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
One of the principal food suppliers in some countries is rice, not limited to Indonesia. The need for rice is predicted to continue to increase annually as rice consumers increase. Rice treatment should be used properly. But not all refined rice will be consumed. It's because of the ill-fitting measures which tend to become food waste. In order to alleviate the problem, it required a tool that calculated the precise ratio of rice and water and could predict the quality of rice maturity. On the study, the weight of rice and the volume of water became the key sharer in the classification of rice maturity levels. Thus, loadcell sensors and hx711 modules will be required as weight stabilizers and linear regression as a as a calculation method for making predictions. There are 30 training data and 15 testing data in the testing process. The result was 90% accuracy in weighing rice and water volume with an average computing time was 20,46 seconds.